Anatomy of the Naga City Landslide and Comparison With Historical Debris Avalanches and Analog Models - Lagmay, Alfredo Mahar Francisco; Escape, Carmille Marie; Ybañez, Audrei Anne; Suarez, John Kenneth; Cuaresma, Genaro (Frontiers in Earth Science, 2020)
Debris avalanches pose some of the most destructive geologic hazards that threaten both urban and rural populations around the world. On 20 September 2018, villages in Naga City, Cebu, Philippines, were devastated by a landslide that claimed 78 lives with 6 missing, joining other catastrophic landslides in the country like the 1628 Iriga and the 2006 Guinsaugon debris avalanches. Understanding the mechanism of these gargantuan landslides and their correct nomenclature are useful for hazard prevention and mitigation. In this study, we compare the deposit characteristics of the Naga City landslide with analog models and well-known historical debris avalanche events/deposits in the Philippines to understand factors that led to the landslide disaster in Naga City. Physical characteristics obtained from aerial and satellite imagery, ground surveys, recorded footage, borehole data, and lithologic maps provided a detailed dataset for analyzing the conditions that led to the mass movement and the observed characteristics of the Naga landslide deposits. Comparison with analog models of hummock formation and the description of historical debris avalanche deposits show striking similarities, which were used to demonstrate that the Naga landslide was a Rockslide-Debris Avalanche. The equations of Corominas (1996) and Dade and Huppert (1998) for long-runout rockfalls support this analysis. The Naga landslide event is an example of a well-documented debris avalanche, complete with all the characteristics of this type of rapid mass movement. It is consistent with the descriptions found in the literature with respect to its deposit features and mechanical behavior as defined by laboratory models and empirically-derived equations. This study helps us understand historical and future long-runout debris avalanches in order for scientists and authorities to find ways to save lives. Unfortunately, there was lack of appropriate hazards assessment on the site, which had warnings in the form of the development of fractures at the headscarp of the landslide, a month prior to the disaster.